Bridging Urban Gaps Through Strategic Digital Infrastructure in Sulaymaniyah City: Menjembatani Kesenjangan Perkotaan Melalui Infrastruktur Digital Strategis di Kota Sulaymaniyah - Al-Douri, Fatima Ibrahim Tuamah (Procedia of Social Sciences and Humanities, 2025)
The study examines how digital infrastructure affects urban life in Sulaymaniyah through its evaluation of the relationships between urban development and public services and digital economic progress. The evaluation of digital infrastructure distribution requires analysts to merge quantitative and qualitative methods along with GIS technology data processing for assessing urban quality of life. The research investigates Sulaymaniyah to reveal the operational mechanism of smart city policies through an assessment of their roles in developing sustainable urban growth with digital infrastructure. The fundamental outcomes from digital infrastructure expenditures enhance quick service delivery speed and enable partnerships that help sustain urban development zones. Public authorities should create supportive policies for digital transformation and form partnerships between public and private organizations to develop urban digital infrastructure according to the document. Highlights: Integration of Methods: Evaluating digital infrastructure in Sulaymaniyah requires both qualitative and quantitative analysis, supported by GIS technology. Smart City Focus: The study explores how digital infrastructure supports sustainable urban growth and the implementation of smart city policies. Policy and Partnerships: Effective urban digital development depends on supportive public policies and collaboration between public and private sectors. Keywords: Digital Infrastructure, Digital Transformation, Smart Cities, Urban Development, Geographic Information Systems (GIS).